2013
DOI: 10.1111/bju.12014
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐specific effect of smoking on upper tract urothelial carcinoma outcomes

Abstract: Objective• To evaluate the gender-specific differential effects of smoking habits and cumulative smoking exposure on outcomes in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). Patients and Methods• A total of 864 consecutive patients, comprising 553 (64%) men and 311 (36%) women, from five international institutions underwent RNU without neoadjuvant chemotherapy.• Smoking history included smoking status (current, former or never), quantity of cigarettes per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 39 publications
(67 reference statements)
0
15
3
1
Order By: Relevance
“…However, no significant association has been identified between gender and CSS when assessing the initial postoperative risk [2]. Other studies have suggested that women could have decreased CSS when stratifying gender analyses by age or smoking habits [22,23]. Our findings highlighted that, although gender did not have an impact on CSS at baseline, female sex was an independent risk factor of poorer long-term CSS rates in >3-yr survivors.…”
Section: Discussioncontrasting
confidence: 53%
“…However, no significant association has been identified between gender and CSS when assessing the initial postoperative risk [2]. Other studies have suggested that women could have decreased CSS when stratifying gender analyses by age or smoking habits [22,23]. Our findings highlighted that, although gender did not have an impact on CSS at baseline, female sex was an independent risk factor of poorer long-term CSS rates in >3-yr survivors.…”
Section: Discussioncontrasting
confidence: 53%
“…20 The effects of smoking on the age at the diagnosis of UTUC remain controversial. [21][22][23] In Japan, the mean age at the diagnosis of UTUC is approximately 5 years earlier for current smokers compared with current non-smokers (P < 0.0001). 24 It should also be noted that the impact of smoking on UTUC outcomes seems to be gender-specific.…”
Section: Cigarette Smokementioning
confidence: 99%
“…Women who are current and heavy long-term smokers were reported to have worse survival outcomes than their male counterparts. 23 …”
Section: Cigarette Smokementioning
confidence: 99%
“…Furthermore, the quantity of cigarettes per day and smoking duration were not captured separately and therefore, we could not use previously validated smoking status classifications such as the ''cumulative smoking exposure.'' 30 In addition, the accuracy of smoking cessation in the NSQIP has not been quantified or validated. Moreover, several surgical confounders, such as surgeon volume, surgical technique, and tumor characteristics, are not accounted for in the NSQIP.…”
Section: Commentsmentioning
confidence: 99%